PENERAPAN E-MODUL BERMUATAN SUSTAINBLE AWARENESS (E-MOBSA) UNTUK MENINGKATKAN KESADARAN BERKELANJUTAN DAN KREATIVITAS PESERTA DIDIK - Zulkarnaen, - (2023)
Sustainable Awareness and Creativity Zulkarnaen Zulkarnaen, Riandi Riandi, Amprasto Amprasto Postgraduate Biology Education Study Program UPI Email: zkarnaen47@gmail.com Abstract This study aims to analyze the effect of implementing E-Modules with Sustainable Awareness (E-Mobsa) on students' sustainable awareness and analyze the effect of E-Modules with Sustainable Awareness (E-Mobsa) on students' creativity. The research method used is a quasi-experimental research method with a research design Nonequivalent control group design on sustainable awareness variables, while the creativity variable uses a posttest-only research design with nonequivalent groups. Then a different test is performed on the average difference in sustainable awareness and creativity. The different tests used were the unpaired t test on the variable sustainable awareness and the Mann Whitney test on the creativity variable. The hypothesis on the sustainable awareness variable was rejected because the sig. (2-Tailed) > 0.05 with unpaired t test. This shows that there is no difference in students' ongoing awareness between the control class and the experimental class after being given E-Mobsa. The hypothesis on the creativity variable was accepted because the Asymp.sig value. (2-Tailed) < 0.05 with Mann Whitney. This shows that there is difference in the creativity of students between the control class and the experimental class after being given E-Mobsa. The reason for the absence of an average difference in the continuous awareness of students in the experimental class and the control class is the lack of interest, motivation and concentration of students towards E-Mobsa. This is because students are not used to independent learning and structured assignments. The reason for the absence of an average difference in students' creativity is the lack of positive routines, micromastery abilities, positive mental attitude. In addition, students have obstacles in the form of no encouragement to explore, schedules that are too tight, the teaching and learning process uses a teacher center approach, and students are not serious about learning.